Tools and techniques for developing tephra stratigraphies in lake cores: A case study from the basaltic Auckland Volcanic Field, New Zealand. (1st September 2015) - Hopkins, Jenni L.; Millet, Marc-Alban; Timm, Christian; Wilson, Colin J.N.; Leonard, Graham S.; Palin, J. Michael; Neil, Helen
Abstract: Probabilistic hazard forecasting for a volcanic region relies on understanding and reconstructing the eruptive record (derived potentially from proximal as well as distal volcanoes). Tephrostratigraphy is commonly used as a reconstructive tool by cross-correlating tephra deposits to create a stratigraphic framework that can be used to assess magnitude–frequency relationships for eruptive histories. When applied to widespread rhyolitic deposits, tephra identifications and correlations have been successful; however, the identification and correlation of basaltic tephras are more problematic. Here, using tephras in drill cores from six maars in the Auckland Volcanic Field (AVF), New Zealand, we show how X-ray density scanning coupled with magnetic susceptibility analysis can be used to accurately and reliably identify basaltic glass shard-bearing horizons in lacustrine sediments and which, when combined with the major and trace element signatures of the tephras, can be used to distinguish primary from reworked layers. After reliably identifying primary vs. reworked basaltic horizons within the cores, we detail an improved method for cross-core correlation based on stratigraphy and geochemical fingerprinting. We present major and trace element data for individual glass shards from 57 separate basaltic horizons identified within the cores. Our results suggest that in cases where major element compositions (SiO2, CaO, Al2 O3, FeO, MgO) do not provide unambiguous correlations, trace elements (e.g. La, Gd, Yb, Zr, Nb, Nd) and trace element ratios (e.g. [La/Yb]N, [Gd/Yb]N, [Zr/Yb]N ) are successful in improving the compositional distinction between the AVF basaltic tephra horizons, thereby allowing an improved eruptive history of the AVF to be reconstructed. Highlights: Basaltic tephra in lake cores are identified through X-ray and magnetic susceptibility analysis. Geochemistry coupled with these techniques highlights regions of tephra reworking within the cores. Primary deposits are reduced in thickness through identification of reworked sections. The trace element signatures of glass shards are more individual than major element signatures. Improved correlations and horizon details for tephras of the Auckland Volcanic Field are outlined.